2018
DOI: 10.29252/ijrm.16.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of cerium oxide nanoparticle on sperm quality and oxidative damage in malathion-induced testicular toxicity in rats: An experimental study

Abstract: Background:Malathion is an organophosphorus pesticide that commonly used in many agricultural and non-agricultural processes. Previous studies have reported the effects of melatonin on the reproductive system. Cerium dioxide nanoparticles (CeNPs) due to their antioxidative properties are promising to impact on the development of male infertility.Objective:The aim of this study was to evaluate the effect of CeNPs on oxidative stress and sperm parameters after malathion exposure of male rats.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
5
30
0
1
Order By: Relevance
“…The results of this study showed that CeNPs at a dose of 60 mg/kg may be slightly toxic. The protective effect of CeNPs was also studied after exposure to malathion subchronic in reproductive system (28). Hence the clinical value of this study is also confirmed.…”
Section: Discussionsupporting
confidence: 59%
“…The results of this study showed that CeNPs at a dose of 60 mg/kg may be slightly toxic. The protective effect of CeNPs was also studied after exposure to malathion subchronic in reproductive system (28). Hence the clinical value of this study is also confirmed.…”
Section: Discussionsupporting
confidence: 59%
“…Many other in vivo and in vitro studies in animals supported the oxidative stress theory (Moridi et al 2018;Arab et al 2018); MAL-induced oxidative stress was also recently observed in many types of human cells (Durak et al 2009;Tuzcu et al 2014;Yan et al 2019;Shieh et al 2019). They found that MAL treatment leads to enhanced production of reactive oxygen species (ROS) and subsequent lipid peroxidation (Durak et al 2009;Bhardwaj et al 2018).…”
Section: Pharmacodynamics Of Malathionmentioning
confidence: 87%
“…Male factor infertility can result from a low sperm count, poor sperm quality, or both. According to global statistics, about 15% of couples suffer from infertility-related issues, and in 50% of these couples, the male partner is affected by aberrations in sperm properties, count, vitality, and morphology [103,104]. This fact underscores the need to develop novel methodologies for the early identification of the causes of infertility and approaches for the personalized treatment of infertility.…”
Section: Nano-based Approaches For Treatment and Diagnosis Of Male Inmentioning
confidence: 99%
“…In this aspect, nanotechnology has come to the forefront in recent years, offering better solutions for infertility related issues. One such solution was described in the work of Moridi et al [ 105 ], who found that the deleterious effect of malathion, a common organophosphorus pesticide, on the male reproductive system was remarkably reduced by the application of cerium dioxide nanoparticles (CeNPs). Restoration of testicular changes was observed upon treatment with CeNPs in malathion-exposed male rats, and the nanoparticles exerted a protective effect on sperm count, motility, and viability.…”
Section: Pursuit Of Nanotechnology In Reproductive Medicine: Accomplimentioning
confidence: 99%